Absorptive Capacity, Green Entrepreneurship, and Sustainable Human Capital Effects on Green Innovation in SMEs - Selly Novela; Ahmad Giffari; Muhammad Khairul Nizam; Akmal Ihsan (Goodwood Publishing, 2025)
Purpose: This study utilizes existing research on knowledge capabilities and firms’ Natural Resource-Based View (NRBV) to explore how absorptive capacity and green entrepreneurship orientation influence green innovation. Additionally, it examines the mediating influence of sustainable human capital within this context. Methods: This study was conducted using an associative design and a quantitative approach. The number of samples gathered was 100 valid respondents, and the questionnaire was spread online. The data collected will then be processed and analyzed with the PLS-SEM analysis using SmartPLS software. Results: The results revealed that green entrepreneurship orientation significantly predicted both sustainable capability and the adoption of green innovation. Additionally, sustainable human capital is a critical determinant of green innovation adoption. Surprisingly, absorptive capacity did not significantly influence green innovation. Hence, several hypotheses were proven to be correct. Conclusion: The results indicate that increasing R&D investment, e-commerce employment, and transaction volume can significantly boost Indonesia's economic growth, demonstrating the importance of these factors in driving the digital economy’s growth. Limitations: This study was limited to SMEs in Greater Jakarta with small samples. Contribution: These results have several implications for SMEs to further enrich the understanding of how the Natural Resource-Based View (NRBV) and relational theory facilitate adaptation to green innovation.